EFEKTIVITAS MEDIA SOSIAL SEBAGAI MEDIA PEMASARAN POLIBATAM PRESS - Nanik Lestari; Alimul Qadri (Politeknik Negeri Batam, 2021)
The focus of this study about the effectiveness of social media as a medium for the Polibatam Press. The research report on this study was conducted on customers & social media that Polibatam Press uses, namely Instagram, Facebook, Youtube, Twitter & WhatsApp as marketing media. The purpose of this research is to find out what social media has the greatest effect on Polibatam Press. The research method that the writer uses is descriptive analysis method and the data collection method is done by survey techniques and documentation analysis, while the survey was conducted using google form with a total of 17 respondents who were surveyed. The results of this study indicate that Instagram is the most effective social media used as a marketing medium for Polibatam Press at this time based on the results of a survey with customers, namely Instagram Polibatam Press, used by 64.7%, subscribers, known by 82% of customers and followed by 53% of customers and from the results of the Instagram documentation analysis can reach 490-550 accounts. As well as Instagram is a social media that directs customers to use Polibatam Press services because many customers know Instagram Polibatam Press and displays complete information.